PERILAKU TANTRUM DAN UPAYA PENANGGULANGAN BAGI ANAK DENGAN GEJALA ADHD DI TK SAKINAH 1 CIBADAK (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Tantrum behavior is a form of emotional outburst commonly found in early childhood, particularly in children with symptoms of Attention Deficit Hyperactivity Disorder (ADHD). This condition is characterized by difficulties in emotional regulation, impulsivity, and hyperactivity, which affect children’s social behavior in school settings. This study aims to identify the forms of tantrum behavior and the efforts made by teachers to manage children with ADHD symptoms at TK Sakinah 1 Cibadak. The research method used is descriptive qualitative, with data collection techniques including observation, interviews, and documentation. The research subjects consist of teachers and children exhibiting ADHD symptoms. The results show that tantrum behaviors include excessive crying, screaming, throwing objects, and difficulty being controlled. The intervention strategies applied include individual approaches, positive reinforcement, distraction techniques, and collaboration with parents. The conclusion of this study is that appropriate and consistent handling can reduce the frequency and intensity of tantrum behavior in children with ADHD symptoms.